If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -2Inx = 0 Solving 1 + -2nxI = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2nxI = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2nxI = 0 + -1 -2nxI = 0 + -1 Combine like terms: 0 + -1 = -1 -2nxI = -1 Divide each side by '-2xI'. n = 0.5x-1I-1 Simplifying n = 0.5x-1I-1
| 3/t=8/3 | | 6x-1/y=5 | | 7/11=5/n | | 7/t=11/7 | | 7t=11/7 | | -10+2w=-6 | | -11y+5y=14 | | 6/y=3/7 | | 3+77x=44x+6 | | 32-15x=-18+9 | | 11/10=y/12 | | 4k+33=1-3k | | 8g-5w=4 | | a/10=4/9 | | 4a^9+5=8 | | 7+5y-4=6y+6-2y | | 3*(3-x)=5x+27 | | 7x-42=2x+12 | | 4x+10=-35-5 | | 1j^5-7=12 | | X-10=-4X | | 5b^2-36b=32 | | a+f=10 | | 1k+q=8 | | 3+10x=-6+x | | 2x-4=5x-12 | | 47x+(-13y)=0 | | 2t+2s=3b | | 36=96%.x | | 36=96%xX | | y=-8x+400 | | 2530=15 |